Hoco : Density Housing Construction & Costs - Fernández Per, Aurora (A+ T Density Series, 2009)
Adamo - Faiden Arquitectos / Buenos Aires - Aguinaga y Asoc. Arquitectos / Madrid - Allford Hall Monaghan Morris / London - Ana Architect / Amsterdam - Arons en Gelauff Architecten / Groeningen - Atelier Kempe Thill / Amsterdam - Ava Architects / Porto - Beckmamm-n' Thépé Architectes / París - Bevk Perovic Architekti / Ljubljana - Bevk Perovic Architekti / Maribor - Big + JDS / Copenhagen - Coll - Leclerc Arquitectos / Lleida - Dosmasuno Arquitectos / Madrid - dRMM / London - Edouard François / Paris - Emmanuel Combarel Dominique Marrec Architects / Paris - Foreign Office Architects / Madrid - Frei Architekten / Rohr - Gigon - Guyer / Zurich - Hamonic + Masson / Paris - HVDN Architecten / Amsterdam - Kasper Danielsen Architects / Future Systems / Copenhagen - Koko Architektid / Tallinn - Lehmann Fidanza & Associés / Fribourg Ch.- López - Rivera Arquitectos / Barcelona - MVRDV, Blanca LLeó / Madrid - Office dA, Burt Hill / Boston - Ofis Arhitekti / Cerklje - Onion Flats / Philadelphia - Poolen Architekten / Culemborg - Roldán + Berengué / Barcelona - Urbanus Architecture & Design / Guangzhou.cn